2015
DOI: 10.1002/2014ja020027
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the energy‐dependent response of riometer absorption

Abstract: Ground-based riometers provide an inexpensive means to continuously remote sense the precipitation of electrons in the dynamic auroral region of Earth's ionosphere. The energy-dependent relationship between riometer absorption and precipitating electrons is thus of great importance for understanding the loss of electrons from the Earth's magnetosphere. In this study, statistical and event-based analyses are applied to determine the energy of electrons to which riometers chiefly respond. Time-lagged correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 77 publications
2
22
0
Order By: Relevance
“…It is therefore possible that the lower energies being precipitated from the injection are contributing to 10.1029/2018JA025588 Journal of Geophysical Research: Space Physics the diffuse aurora, which may also explain the correlation between the two signatures. We point out, however, that although Kellerman et al (2015) showed 10-keV electrons may affect riometer signals, the 40-to 60-keV population was much more likely to affect the riometer signature. In either case, the fluctuations we see at RANK may indeed be due to particle precipitation caused by the narrow, earthward-traveling DFBs embedded in bursty bulk flows that we observe as an equatorwardmoving streamer in the RANK ASI.…”
Section: Riometer Absorption With Asi Countsmentioning
confidence: 67%
See 2 more Smart Citations
“…It is therefore possible that the lower energies being precipitated from the injection are contributing to 10.1029/2018JA025588 Journal of Geophysical Research: Space Physics the diffuse aurora, which may also explain the correlation between the two signatures. We point out, however, that although Kellerman et al (2015) showed 10-keV electrons may affect riometer signals, the 40-to 60-keV population was much more likely to affect the riometer signature. In either case, the fluctuations we see at RANK may indeed be due to particle precipitation caused by the narrow, earthward-traveling DFBs embedded in bursty bulk flows that we observe as an equatorwardmoving streamer in the RANK ASI.…”
Section: Riometer Absorption With Asi Countsmentioning
confidence: 67%
“…In fact, Sivadas et al (2017) showed that 10to 100-keV fluxes are enhanced over discrete aurora. That said, Kellerman et al (2015) showed that energies as low as 10 keV can affect riometer absorption, so we cannot rule out the possibility of overlapping populations. It is therefore possible that the lower energies being precipitated from the injection are contributing to 10.1029/2018JA025588 Journal of Geophysical Research: Space Physics the diffuse aurora, which may also explain the correlation between the two signatures.…”
Section: Riometer Absorption With Asi Countsmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been long recognized that energetic particles at geosynchronous Earth orbit (GEO) are modulated by solar wind forcing (e.g., Paulikas and Blake 1979;Baker et al 1979Baker et al , 1986Baker et al , 1990Blake et al 1997;Reeves 1998;Mathie and Mann 2001;O'Brien et al 2001;Li, 2001Li, , 2004Li et al 2005Li et al , 2011Lyatsky andKhazanov 2008a, 2008b;Borovsky and Denton 2009;Boynton et al 2013;Simms et al 2016;Kellerman et al 2015). Paulikas and Blake (1979), for example, analyzed energetic electron data from ATS-1, ATS-5 and ATS-6 spacecraft and found a pronounced positive correlation between the electron fluxes and solar wind speed.…”
Section: Solar Wind Driversmentioning
confidence: 99%
“…The mechanism behind the riometer principle involves enhanced electron density produced in the D region ionosphere, causing increased electron collision rates with sufficient frequency to attenuate HF radio waves transiting the atmosphere. Riometers can be used in event and statistical studies (e.g., Baker et al 1981;Spanswick et al 2007) and can also be used in infer temporal evolution of population fluxes from the overlying magnetosphere (Kellerman et al 2015). Riometer technology has evolved from simpler wide beam systems to analog and now digital beam forming, wide frequency capture imaging systems, with the latter providing much better measurement precision and/or much higher spatial resolution for temporal and spatial precipitation loss studies (e.g., Honary et al 2011).…”
Section: Loss Mechanismsmentioning
confidence: 99%